2021
DOI: 10.1094/mpmi-10-20-0271-r
|View full text |Cite
|
Sign up to set email alerts
|

AKSF1 Isolated From the Rice-Virulent Strain Acidovorax avenae K1 Is a Novel Effector That Suppresses PAMP-Triggered Immunity in Rice

Abstract: Microbial pathogens deliver effectors into plant cells to suppress plant immune responses and modulate host metabolism in order to support infection processes. We sought to determine if the Acidovorax avenae rice-virulent K1 strain can suppress pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) induced by flagellin isolated from the rice-avirulent N1141 strain. The flagellin-triggered PTI, including H2O2 generation, callose deposition, and expression of several immune-related genes were stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Moreover, sequence analysis of regions flanking the transposons revealed that they were inserted into 68 different genes. In addition, multiple proteins were secreted by strains N1141 and K1 using their T3SS (Kondo et al, 2017;Kawaguchi et al, 2021). The presence of multiple effectors in A. avenae strains N1141 and K1 raises the question of whether NRHIF and KRHIF are the only ETI-inducible effectors for rice and finger millet, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, sequence analysis of regions flanking the transposons revealed that they were inserted into 68 different genes. In addition, multiple proteins were secreted by strains N1141 and K1 using their T3SS (Kondo et al, 2017;Kawaguchi et al, 2021). The presence of multiple effectors in A. avenae strains N1141 and K1 raises the question of whether NRHIF and KRHIF are the only ETI-inducible effectors for rice and finger millet, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…When rice plants were inoculated with AKSF1-disruption mutants, disease symptom severity was reduced and bacterial growth was suppressed. These results indicate that AKSF1 is a novel effector that can suppress PTI in host rice plants (Kawaguchi et al, 2021). Interestingly, whole-genome sequencing of strain N1141 revealed that it lacks AKSF1.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Effectors from T3SS1 are generally detected earlier in the infection process and it has been suggested that they are more involved with the earlier stages of the vacuole maturation while effectors from T3SS2 are more involved with later stages [ 87 ]. Finally, experiments using mutants of Acidovorax avenae identified an effector protein ( A. avenae K1 suppression factor 1) that was associated with supressing the cellular response following recognition of flagellin associated molecular patterns [ 88 ].…”
Section: The T3ssmentioning
confidence: 99%